Communicating the risk of dementia: a scoping review - Lee Smith; Damiano Pizzol; Benjamin R Underwood; Maja Swirska; Axel A S Laurell; Emad Sidhom (BMJ Neurology Open)
Background Dementia is a syndrome characterised by progressive cognitive and functional decline arising from a neurodegenerative disease. Genetic testing, imaging and fluid biomarkers mean that levels of risk of dementia diagnosis are becoming frequent and complex. How risk is communicated in this context is an increasingly important topic.Aims The aim of this scoping review is to map the existing literature regarding the components of risk communication, the factors influencing its outcomes and the guidelines developed to support clinicians in this process.Methods This is a systematic scoping review addressing the communication of risk to individuals living with or at risk of dementia, as well as perspectives of family, carers and healthcare professionals.Results 115 articles were identified, including genetic (n=41), amyloid (n=45) and other biomarkers (n=9). Patients expressed a desire to be informed about their risk of developing dementia, listing future planning and participation in clinical research as benefits of disclosure. While risk disclosure did not significantly impact anxiety or depression, it was associated with increased event distress among participants identified as elevated risk. Individuals at high risk frequently overestimated their likelihood of developing dementia. Tools and guidelines that have supported clinicians in risk disclosure emphasised the use of educational materials, clear communication about risk and prognosis, and regular follow-up appointments. Gaps in literature include blood biomarkers, non-Alzheimer’s disease dementias and communication to people with cognitive impairment.Conclusions Risk communication is a crucial topic for healthcare professionals, especially since the emergence of novel techniques to predict dementia.